Effect of space fillers in brake friction composites on airborne particle emission: A case study with BaSO4, Ca(OH)2, and CaCO3. (January 2022) - Park, Jongsung; Gweon, Jaehyun; Seo, Hyungjo; Song, Wansu; Lee, Donggyu; Choi, Jinsoo; Kim, Yun Cheol; Jang, Ho
Abstract: This study investigated particulate matter (PM) produced during brake application, focusing on the effect of space fillers in low-steel friction composites. The composites ranked in terms of brake emissions in a descending order were BaSO4, Ca(OH)2, and CaCO3 . CaCO3 produced thicker friction films on the steel fibres than Ca(OH)2, whereas bare steel fibres were found with BaSO4, indicating strong effects of the filler-dependent coverup layers, which was confirmed by microhardness tests. The filler effect on PM suggests that proper selection of space fillers can reduce brake emissions from grey iron discs by preventing direct adhesion with steel fibres. Highlights: Brake emission, disc wear, and pad surface were affected by filler type. The steel fiber on the pad with CaCO3 is covered with wear particles. The direct contact between disc and steel fiber on the pad with BaSO4 was generated. The pad with BaSO4 indicate higher PM due to higher wear loss of brake disc.